2008
DOI: 10.1302/0301-620x.90b12.21198
|View full text |Cite
|
Sign up to set email alerts
|

Osteotomies around the knee

Abstract: New developments in osteotomy techniques and methods of fixation have caused a revival of interest of osteotomies around the knee. The current consensus on the indications, patient selection and the factors influencing the outcome after high tibial osteotomy is presented. This paper highlights recent research aimed at joint pressure redistribution, fixation stability and bone healing that has led to improved surgical techniques and a decrease of post-operative time to full weight-bearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
159
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(184 citation statements)
references
References 67 publications
2
159
1
6
Order By: Relevance
“…Similar results have been demonstrated with both opening-wedge and closing-wedge varus-producing distal femoral osteotomy (DFO) for valgus alignment and isolated lateral compartment knee OA, with a mean survival rate of 80% at 10-year follow-up 13. Indications for realignment osteotomy of the knee have broadened over the past 10–15 years to include patients with knee instability and as adjuvant procedures to unload compartments during meniscus and cartilage restoration 14. In these latter cases, the osteotomy functions by providing an optimal biomechanical environment to address ligament instability, while also offloading the articular surface in the affected compartments to potentially prevent or delay the progression of OA 15…”
Section: Introductionmentioning
confidence: 62%
“…Similar results have been demonstrated with both opening-wedge and closing-wedge varus-producing distal femoral osteotomy (DFO) for valgus alignment and isolated lateral compartment knee OA, with a mean survival rate of 80% at 10-year follow-up 13. Indications for realignment osteotomy of the knee have broadened over the past 10–15 years to include patients with knee instability and as adjuvant procedures to unload compartments during meniscus and cartilage restoration 14. In these latter cases, the osteotomy functions by providing an optimal biomechanical environment to address ligament instability, while also offloading the articular surface in the affected compartments to potentially prevent or delay the progression of OA 15…”
Section: Introductionmentioning
confidence: 62%
“…Among all included studies in this present study, five trials applied OWHTO, seven trials used CWHTO, and one study used hemicallotasis. OWHTO is considered safe and easy [21, 48, 49] based on the assumption that CWHTO may be associated with a higher incidence of complications, especially peroneal nerve paralysis. Despite improved surgical techniques and implant design, previous studies have reported complications after UKA, such as loosening of the tibial or femoral component or osteoarthritic changes in the development of the lateral compartment due to antero–posterior instability of the knee, which leads to rapid wearing of the polyethylene insert [11, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Medial osteoarthritis of the knee can be treated with open-wedge,valgus, high tibial osteotomy (OW-HTO) (Brinkman et al 2008). There are concerns, however, regarding the ability of the fixation technique to withstand the forces that act on the proximal tibia (Brinkman et al 2008).…”
Section: Introductionmentioning
confidence: 99%